Role of urinary podocalyxin in early diagnosis of diabetic nephropathy - Kostovska Irena; Trajkovska Katerina Tosheska; Cekovska Svetlana; Topuzovska Sonja; Kavrakova Julijana Brezovska; Spasovski Goce; Kostovski Ognen; Labudovic Danica (Sciendo, 2020)
Introduction. Podocyte injury has been reported as an early feature of DN therefore, the assessment of podocyte injury can be accomplished by estimation of podocalyxin in urine. This study aimed to estimate the urinary podocalyxin levels and to determine the sensitivity and specificity of this biomarker for early detection of DN.